Peculiarities of Elite’ Image Formation In Lithuanian Mass-Media - Kučinskė, Irina (Sociologija. Mintis ir veiksmas, 2005)
After the collapse of Soviet system, mass-media in Lithuania became the concomitant element of democracy. However, with the great reliance by society upon and with the enlarged influence of mass-media, it could become not only the scene where formation of cultural and social values of society take place, but, failing to establish an efficient supervision, an autocratic former of public opinion as well. The authority, carried by mass-media, enables it to create different images, which, if the audience fails to be critical, could be treated as real. Means of mass-media form agenda setting by paying greater attention to some of the topics and leaving the other ones behind, however, the elite of the society always has been one of the subjects of mass-media. The relation between mass-media and elite has not been broadly explored yet, therefore the main purpose of this paper is to analyze how the image of elite in Lithuanian mass-media is formed. The research is based on content analysis of national daily newspapers „Lietuvos Rytas“ and „Vakaro zinios“ published during December 2003. The investigation revealed, that „Vakaro zinios“, which represents the yellow-press, openly divides society into „elite“ and „the masses“ and uses this division actively in it’s pages. This contraposition is extremely emphasized and highlighted by the huge and expressive headlines, comments on photoprints. „Lietuvos rytas“, which aims at representing the solid mass-media, also shows existing confrontation between social segments, however it avoids emphasizing this by giving clearly expressed titles to these segments. During the second research the image of elite was explored in „Stilius“, a weekly supplement of „Lietuvos rytas“, which in several years became the publication, reflecting in chronological order the lifestyle of Lithuanian elite. The investigation of photoreporting of public events in 1998-2005 „Stilius“ revealed an active process of formation of the image of elite. „Stilius“ brought elite into publicity, introduced the lifestyle of elite to society, sorted and presented persons, belonging to elite, to society. There was no publication in Lithuania before „Stilius“, which would show so visually and clearly who forms the elite, what persons belong to it, how they are different. The portrayal of their luxurious lifestyle became one of the features, representing elite. In summary, could be proposed that Lithuanian mass-media, carrying great reliance of society and using it’s influence, actively forms the image of Lithuanian elite, using it to catch the attention of audience. The image of elite, created by mass-media, in case of social tension, could influence the hostility of lower segments of society for the elite.
Keywords: elite; image; mass-media